PENERAPAN KURIKULUM BERBASIS KKNI PADA PEMASARAN SYARIAH DAN AREA KERJA PEMASARAN PADA PERGURUAN TINGGI ISLAM TAHUN 2021 - Muhammad rifai, Muhammad rifai; Moch Irwan Hermanto, Moch Irwan Hermanto; Rahmi Rismayani Deri, Rahmi Rismayani Deri; Abdussalam, Abdussalam; Dila Sekar Arum Sari, Dila Sekar Arum Sari (Media Nusantara, 2024)
Universities in the Tri Dharma universities at the Nusantara Islamic University (UNINUS) and the Nahdlatul Ulama School of Economics(STIENU) are highly expected to carry out research in developing appropriate technology and expertise that can build a community empowerment economy that is beneficial for development in a region. This research focuses on research regarding the concept of competency-based education in Sharia Marketing and Marketing Work Area courses. This course is very important to be developed according to the KKNI because it contains fulfillment of the State's needs in the development of Sharia Marketing, Marketing Science and the development of Islamic-based logistics and distribution. Development for the industrial world in filling students' competency dimensions. Once the competencies of PT graduate students begin to be honed, it is hoped that students/graduates will be able to apply and teach them to the community in the form of developing non-formal vocational education so that both PT students/graduates will maintain their competency and the community will feel that their ability to face the job market and be able to create jobs will increase. together, which has an impact on increasing income for the community and reducing unemployment rates in the community.